(untitled) (Journal of Shaheed Suhrawardy Medical College, 2022)
Background: The safety and efficacy of the postpartum intrauterine device (PPIUD) has been documented worldwide with increasing institutional deliveries. It was relative new concept therefore a close observation should be kept on potential complication arising from it. Removal of an IUD can be easily done when the string is visible during speculum examination but the task become challenging when the string no longer visible. Objectives: To evaluate the role of hysteroscopy for removal of PPIUD with missing string. Methods: This descriptive study was conducted in tertiary government hospital over six months from July 2020 to December 2020. PPIUD clients with lost strings were included in this study. Before the procedure complete history about reason for retrieval, duration of insertion, complication related to IUD was recorded. Furthermore, speculum examination & USG was performed then decided for hysteroscopic evaluation and removal. Per-operative location of PPIUD in uterine cavity and any complication & associated pathology encountered were recorded. The size and model of hysteroscope also noted. Results: Thirty one patients were included among them more than two third of PPIUD given following caesarean section (LSCS). Reason for PPIUD removal of most clients due to menstrual irregularities 29% displaced & fragmented CuT on USG 25.8% and desires for pregnancy. Nineteen respondents removed within three years due to complication like irregular menses ,displaced IUD on ultrasonography.. Most of the PPIUD 64.5% in normal location rest of them deviated from normal among those three PPIUD were inverted & tip of the five PPIUD near the external os. Arms of cu-T were embeded in five clients, some difficulties faces to remove those. Polyp were found in two clients with menstrual irregularities. Postoperative outcome of all patients were uneventful. Conclusion: Hysteroscopy is a good modality for the removal of PPIUD with lost strings. J Shaheed Suhrawardy Med Coll 2021; 13(1): 63-67